Potency of Fall Leaves of Bungur (Lagerstroemia loudonii Teijsm. & Binn.) As Alpha-Glucosidase Inhibitor - Riyanti, Soraya; MA, Setyadi; E, Kumolowati (Jurnal Farmasi Udayana; Vol. 10, No 1, Tahun 2021, 2021)
Bungur (Lagerstroemia loudonii Teijsm. & Binn.) belong to the genus Lagerstroemia, family Lythraceae. Corosolic acid is a pentacyclic triterpene group contained in Lagerstroemia speciosa L. leaves and has been reported to reduce blood glucose levels by inhibiting alpha-glucosidase. The ethanol extract of the leaves of bungur (Lagerstroemia loudonii Teijsm. & Binn.) which was still green was reported to have alpha-glucosidase inhibitory activity of 262, 20 µg/mL, ethyl acetate and n-hexane fraction of 62.73 µg/mL and 97.16 µg/mL. This study aimed to determine the inhibitory activity of alpha-glucosidase of ethanol extract of fallen leaf and their fractions. The extraction process by reflux in 96% ethanol, the fractionation process by liquid-liquid extraction. Testing of alpha-glucosidase inhibitor activity using colorimetric method at a wavelength of 401 nm with chromogenic substrate p-nitrophenyl-?-D-glucopyranoside (PNPG) and alpha-glucosidase enzyme from Saccharomyces cerevisiae, acarbose was used as a standard inhibitor alpha-glucosidase. The results showed that the IC 50 values ??of ethanol extract, n-hexane, ethyl acetate and water fraction were 170.39 µg/mL; 258.41 µg/mL; 382.46 µg/mL; and 134.27 µg/mL, and acarbose 14.6 µg/mL. The alpha-glucosidase inhibitory activity of the ethanol extract of the fallen leaves of bungur was greater than that of the ethanol extract of the leaves of bungur which was still green and the water fraction of the fallen leaves gave the greatest alpha-glucosidase inhibition activity with an IC 50 of 134.27 µg/mL.